Return to Golf After Shoulder Arthroplasty: A Systematic Review. Issue 4 (March 2021) - Salem, Hytham S.; Park, Do H.; Thon, Stephen G.; Bravman, Jonathan T.; Seidl, Adam J.; McCarty, Eric C.; Frank, Rachel M.
Background: The number of golfers aged ≥65 years has increased in recent years, and shoulder arthritis is prevalent in this age group. Guidelines for return to golf (RTG) after shoulder arthroplasty have not been fully established. Purpose: To review the data available in the current literature on RTG after shoulder arthroplasty. Study Design: Systematic review. Methods: A systematic review based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines was performed. Two independent reviewers searched PubMed, Embase, and the Cochrane Library using the terms "shoulder, ""arthroplasty, ""replacement, " and "golf." The authors sought to include all studies investigating RTG after total shoulder arthroplasty (TSA), shoulder hemiarthroplasty (HA), and reverse shoulder arthroplasty (RSA). Outcomes of interest included indications for shoulder arthroplasty, surgical technique, rehabilitation protocol, amount of time between surgery and resumption of golf activity, and patient-reported outcome measures. Results: A total of 10 studies were included, 2 of which reported on golf performance after shoulder arthroplasty. The other 8 studies described return to sports after shoulder arthroplasty with golf-specific data for our analysis. Three studies that included patients who underwent TSA reported RTG rates ranging from 89% to 100% after mean follow-up periods of 5.1 to 8.4 months. Two studies included patients who underwent TSA and HA and reported RTG rates of 77% and 100% after mean intervals of 5.8 and 4.5 months, respectively. Two studies included patients who underwent RSA, with RTG rates of 50% and 79% after mean postoperative intervals of 5.3 and 6 months, respectively. One study included only patients undergoing HA, with an RTG rate of 54% and a mean RTG time of 6.5 months. Varying surgical procedures and baseline patient characteristics precluded our ability to draw conclusions regarding surgical technique, rehabilitation protocol, or patient-reported outcome measures among studies reporting these data. Conclusion: Most patients who undergo a shoulder arthroplasty procedure can expect to resume playing golf approximately 6 months after the index procedure. The rate of return may be lower after RSA and HA as compared with anatomic TSA. The data presented in our review can help physicians counsel patients who wish to continue golf participation after a shoulder arthroplasty procedure.